Neuropathic low back pain in clinical practice - Baron, Ralf; Treede, Rolf-Detlef (European journal of pain, 2016)
Background and objective Low back pain (LBP) is one of the most common chronic pain conditions. This paper reviews the available literature on the role of neuropathic mechanisms in chronic LBP and discusses implications for its clinical management, with a particular focus on pharmacological treatments. Databases and data treatment Literature searches were performed in PubMed, key pain congresses and ProQuest Dialog to identify published evidence on neuropathic back pain and its management. All titles were assessed for relevant literature. Results Chronic LBP comprises both nociceptive and neuropathic components, however, the neuropathic component appears under-recognized and undertreated. Neuropathic pain (NP) is challenging to manage. Many patients with chronic LBP have pain that is refractory to existing treatments. Typically, less than half of patients experience clinically meaningful analgesia with oral pharmacotherapies; these are also associated with risks of adverse effects. Paracetamol and NSAIDs, although widely used for LBP, are unlikely to ameliorate the neuropathic component and data on the use of NP medications such as antidepressants and gabapentin/pregabalin are limited. While there is an unmet need for improved treatment options, recent data have shown tapentadol to have efficacy in the neuropathic component of LBP, and studies suggest that the capsaicin 8% patch and lidocaine 5% medicated plaster, topical analgesics available for the treatment of peripheral NP, may be a valuable additional approach for the management of neuropathic LBP. Conclusions Chronic LBP often has an under-recognized neuropathic component, which can be challenging to manage, and requires improved understanding and better diagnosis and treatment. What does this review add? Increased recognition and improved understanding of the neuropathic component of low back pain raises the potential for the development of mechanism-based therapies. Open and retrospective studies suggest that agents like tapentadol and topical analgesics -such as the capsaicin 8% patch and the lidocaine 5% medicated plaster - may be effective options for the treatment of neuropathic low back pain in defined patient groups.
Gesehen am 02.07.2019